Photoluminescence, upconversion and quantum-cutting emission in Tm/Tb/Pr and Yb co-doped oxide phosphor: A comparative study - Singh P.; Shahi P.K.; Singh S.K.; Rai S.B. (My University, 2025)
We have carried out a comparative study of upconversion (UC), photoluminescence (PL) and quantum cutting (QC) emission of three rare-earth activators (Tm, Pr and Tb) in the presence of Yb ion in La2O3 host. IR quantum cutting is of particular importance and has been observed on the principle of energy transfer from a particular lanthanide ion to Yb3+ ions. A UV/visible photon is splitted into two IR photons via the involvement of two Yb3+ ions. Phosphors were prepared by conventional solution combustion method and crystallizes into hexagonal phase of La2O3 having space group P63/mmc. Study summarizes that, La2O3 matrix is a potential host for different lanthanide ions, particularly Tm, Tb and Pr, to achieve the UC, PL and QC emission. The upper limit of NIR quantum cutting efficiency is observed maximum for Tm ion which is 180%, while Pr also gives a similar efficiency value (178%). The upper limit of NIR quantum cutting efficiency for Tb is relatively less (153%), however it is remarkably better than previous reported values. The material could be useful for different optical applications including for spectral modifications. © 2016 Elsevier B.V. All rights reserved.